Biofilm Inhibitory Activity of Nauclea latifolia, Ocimum gratissimum and Garcinia kola Extracts Against Enteroaggregative Escherichia coli (Nigerian Journal of Pharmaceutical Research, 2025)
Background: Enteroaggregative Escherichia coli (EAEC), a biofilm-forming E. coli pathotype, is recognized as one of foremost causes of diarrhea in children under five years old, traveller’s diarrhea and persistent diarrhea. Biofilm complicates treatment as it enhances the pathogen’s ability to undermine host immune responses, often resulting in emergence of resistant mutant.Objectives: In search for potential therapeutic leads against EAEC with less selection pressure, the study was designed to investigate selected medicinal plants for biofilm inhibitory activity against EAEC.Material and Methods: Pulverised dry plant materials of Nauclea latifolia (leaf), Ocimum gratissimum (leaf) and Garcinia kola (seed) were macerated in acetone for 24 hrs. The supernatants were concentrated at reduced pressure and dried in vacuo. Thereafter, varying concentrations (0.31-5.0 mg/mL) of the extracts were evaluated for growth and biofilm inhibitory activities against EAEC 042 strain using the crystal violet-based biofilm assay method. Biofilm inhibitory data were analysed using 2-way ANOVA, while the most bioactive of the extracts was profiled by phytochemical analysis.Results: Nauclea latifolia reproducibly inhibited biofilm formation by greater than 30% (defined biofilm inhibition cut-off) while inhibiting growth by under 10% (defined growth inhibition cut-off). The other two plants showed relatively weak biofilm inhibitory activities. Phytochemical evaluation revealed the presence of alkaloids, tannins, steroids, saponins, flavonoids, and cardiac glycosides.Conclusions: Nauclea latifolia exhibited good biofilm inhibitory activity against EAEC 042 strain with less selection pressure. The plant represents a potential source of novel antibiofilm compounds against enteroaggregative E. coli.